Paradigm Of National Income in Islamic Economy - Hery Purwanto; Siswahadi Siswahadi (Syariati: Jurnal Studi Al-Qur'an dan Hukum, 2021)
Economic growth and development are macroeconomic problems in the long run. Every country has the opportunity to realize economic growth because the factors of the production increase from one period to another and therefore national income can be increased. National income is one of the important variables in macroeconomic discussions. The term national income is a translation of national income (in full, National Income Accounts). National income does not only calculate national income but also calculates expenditures, even for goods and products nationally. These calculations are performed periodically, usually in annual or quarterly units of time. Since national income can mean all income, all expenditure, or all production of goods and services, the calculation can be made based on the type of economic activity. In Islamic economics, national income is measured by the parameter Falah, namely true welfare and welfare. The sources of national income according to Islam are zakat, fai, and ghanimah. In a literal sense, Falah is glory and victory in life. For the life of the world, Falah includes three definitions, namely survival, freedom of desire, and strength and honor. As for the hereafter, Falah includes the meaning of eternal life, prosperity and eternal glory, and eternal knowledge.